Male/Female Differences in Neuroprotection and Neuromodulation of Brain Dopamine - Bourque, Mélanie; Dluzen, Dean E.; Di Paolo, Thérèse (Frontiers in Endocrinology, 2011)
The existence of a sex difference in Parkinson’s disease is observed in several variables, including susceptibility of the disease, age at onset and symptoms. These differences between men and women represent a significant characteristic of Parkinson’s disease which suggests that estrogens may exert beneficial effects against the development and the progression of the disease. This paper reviews the neuroprotective and neuromodulator effect of 17β-estradiol and progesterone as compared to androgens in the nigrostriatal dopaminergic system of both female and male rodents. The 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mice model of Parkinson’s disease and methamphetamine toxicity faithfully reproduce the sex differences of Parkinson’s disease in that endogenous estrogen levels appear to influence the vulnerability to toxins targeting the nigrostriatal dopaminergic system. Exogenous 17β-estradiol and/or progesterone treatments show neuroprotective properties against nigrostriatal dopaminergic toxins while androgens fail to induce beneficial effect. Sex steroids treatments show males and females difference in their neuroprotective action against methamphetamine toxicity. Nigrostriatal dopaminergic structure and function, as well as the distribution of estrogen receptors, show sex difference and may influence the susceptibility to the toxins and the response to sex steroids. Genomic and non-genomic actions of 17β-estradiol converge to promote survival factors and the presence of both estrogen receptors α and β are critical to 17β-estradiol neuroprotective action against MPTP toxicity.